Hungary in World War II : caught in the cauldron - Cornelius, Deborah S. (World War II: the global, human, and ethical dimension, 2011)
The legacy of World War I -- Hungary between the wars -- The last year of European peace -- Clinging to neutrality -- Hungary enters the war -- Disaster at the Don -- Efforts to exit the war -- German occupation -- From arrow cross rule to Soviet occupation -- Postwar Hungary